Optimising Growth, Immunity, and Gene Expression in Broiler Chickens Through Dietary Threonine Levels and Oil Inclusion - Mohamed I. El‐Katcha; Mosaad A. Soltan; Heba I. Ghamry; Abeer F. El‐Nahas; Laila A. Al‐Shuraym; Ostan Mihaela; Rada Olga; Rasha E. Azab; Ahmed Abdeen; Mustafa Shukry; Set A. El‐Shobokshy (Veterinary Medicine and Science)
ABSTRACT Background The inclusion of synthetic amino acids in poultry nutrition plays a crucial role in both enhancing the synthesis of immunoglobulins and elevating the overall comprehensiveness of the amino acid profile. Objectives This research examined the effects of consuming threonine (Thr) in various forms levels with low or high oil on broiler chickens' growth and immunity. Methods We investigate the growth performance, feed efficiency, immune response, intestinal morphology, absorptive capacity, and expression of some genes related to the feed intake (Pro‐opiomelanocortin [POMC]), fatty acid synthesis (Acetyl‐CoA Carboxylase [ACC]), immunity (lipopolysaccharide‐induced tumour necrosis like alpha factor [LITAF]), and heat shock protein 70 (HSP70). Eight groups of chicks were used, including four dietary Thr levels (100%, 115%, 130%, or 145%) with two oil levels (mixture of sunflower 50% and soybean oils 50%): (control) and high. Results The higher dietary Thr level (145%) with high oil inclusion significantly increased ACC and POMC gene expression, resulting in the lowest feed intake, body weight gain (BWG), and liver fat content. Combining high oil with 115% Thr was the optimum for the broilers. The birds have significant (p ≤ .05) growth performance, immune parameters, and intestinal health, as well as the lowest expression of ACC, POMC, HSP70, and LITAF, which was reflected in better feed conversion ratio and lower incidence of fatty liver, thermo‐resistance, and immune status of the birds. Conclusions The combination of high oil and 115% Thr levels optimises broiler health and productivity, enhancing growth, immune function, and gut health. This diet lowers the expression of genes associated with fatty liver and stress, leading to better feed efficiency, thermo‐resistance, and overall well‐being. Adopting these dietary adjustments can improve broiler performance and economic viability in poultry farming by enhancing essential productivity metrics.